Delayed impact of the North Atlantic Oscillation on biosphere productivity in Asia - Wang, Guiling; You, Liangzhi (American Geophysical Union, 2004)
This study examines the relationship between the North Atlantic Oscillation (NAO) and vegetation productivity in Asia inferred from both provincial crop yields data in China and satellite-derived Normalized Difference Vegetation Index data. Our finding suggests that vegetation productivity in northern Asia during the main growing season correlates significantly to NAO, with a surprising long delay of 1.5 years. Correlation at shorter time lags, which was the focus of previous studies, is weak and not significant between the NAO index and vegetation activities in Asia. This suggests the existence of a so-far unrecognized mechanism that carries the NAO signal for multiple years. The lagged vegetation response also provides the potential for NAO to serve as a predictor for crop yields in China.